A new Moenkhausia (Actinopterygii: Characiformes: Characidae) from the upper Rio Negro Basin, Brazil - Lima, Flávio C.T.; Soares, Isabel M. [UNESP] (Magnolia Press, 2018)
A new species of Moenkhausia is described from the upper rio Negro basin, Amazonas, Brazil. The new species is distinguished from all congeners, except M. agnesae, by presenting a color pattern characterized by the presence of two irregularly-shaped humeral blotches, and the presence of dark longitudinal stripes on the dorsal portion of the body. The new species can be readily separated from M. agnesae by presenting longitudinal stripes straight and more conspicuous dorsally, humeral blotches contacting each other, 2–3 tricuspid maxillary teeth, 32–35 lateral-line scales, and length of maxilla 45.3–51.0% in head length.
Keywords: Amazonas state; Color pattern; Moenkhausia agnesae; Rio miuá